2009
DOI: 10.1080/00207540802112652
|View full text |Cite
|
Sign up to set email alerts
|

A generic deadlock-free reactive scheduling approach

Abstract: A hierarchical control system is proposed for automated flexible manufacturing cells (FMC) that operate in a job shop flow setting. The control system is made up of a higher level scheduler/reactive scheduler, which optimizes the production flow within the cell, and a lower level supervisor that implements the decisions of the scheduler on the shop floor. Previous studies have regularly considered the production scheduling and the supervisory control as two separate problems. This has led to: i) deadlock-prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 102 publications
(221 reference statements)
0
8
0
Order By: Relevance
“…Also, on SERVER atom, each SERVER can only process one PRODUCT at a time. Therefore, constraints related to assignment of jobs to only one machine at each stage will be achieved (constraints set by Equations (5) and (6)). Since the simulation model is a mimic of real systems, all constraints related to system availability will automatically be satisfied.…”
Section: Computer Simulation Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, on SERVER atom, each SERVER can only process one PRODUCT at a time. Therefore, constraints related to assignment of jobs to only one machine at each stage will be achieved (constraints set by Equations (5) and (6)). Since the simulation model is a mimic of real systems, all constraints related to system availability will automatically be satisfied.…”
Section: Computer Simulation Modelingmentioning
confidence: 99%
“…Another important factor that has an effect on makespan is interruption caused by machine breakdowns. 5 The most applicable way to deal with machine breakdowns (unknown interruption) is preventive maintenance (PM, i.e., known interruption). On solving the scheduling problem, unavailability of resources is incorporated in the model constraint.…”
Section: Introductionmentioning
confidence: 99%
“…18,32 In this context, a relatively new aspect of cyclic scheduling research are robust scheduling problems. 18,33,34 The aim of this new approach is to develop robust solutions capable of accommodating disruptions during schedule execution. In this study, robustness is understood as the ability of a system to resist change without the need to adjust its initial stable configuration.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al (2005) have proposed dividing the scheduling process into two nonoverlapping parts: predictive before the breakdown occurs, and reactive when the machine is recovered after the breakdown. Fahmy et al (2008) have suggested inserting dummy tasks to remove the affected tasks from the schedule and to later reschedule them. The duration of the dummy task is equal to the recovery time of the broken machine.…”
Section: Job Scheduling and Disruption Problemmentioning
confidence: 99%